2018
DOI: 10.1080/09603123.2018.1429579
|View full text |Cite
|
Sign up to set email alerts
|

The real and subjective indoor environmental quality in schools

Abstract: Investigation of IEQ and subjective evaluation of IEQ by pupils is the main objective of this research work. For the monitoring two classrooms in primary school and two classrooms in art school were chosen. Very high CO levels were determined in both investigated schools. In three of four classrooms the statistically significant differences (p < 0.01) were reported between TVOC levels in autumn and spring. The recommended value for TVOC levels was exceeded in the range from 52 % to 53 % in autumn and from 52 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…However, we would argue that this limitation ought not to be considered a fundamental problem. A cumulative body of research has shown that people can evaluate IEQ relatively accurately [47][48][49]. However, psychosocial factors can also influence perceived IEQ and, therefore, questionnaires cannot be the only tool to evaluate it [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, we would argue that this limitation ought not to be considered a fundamental problem. A cumulative body of research has shown that people can evaluate IEQ relatively accurately [47][48][49]. However, psychosocial factors can also influence perceived IEQ and, therefore, questionnaires cannot be the only tool to evaluate it [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…From the practical point of view, our results support the notion that when self-administered questionnaires are used to evaluate perceived IAQ among students in schools, items measuring psychosocial problems need to be included. Recent research shows that such questionnaires can be useful tools in assessing schools’ IAQ [ 6 , 61 ]. However, it is important to note that students’ psychosocial problems explained only 9–13% of the outcome variables’ total variances.…”
Section: Discussionmentioning
confidence: 99%
“…There are well-documented relationships between building-related factors and subjective IAQ [ 5 , 6 , 7 ] as well as between building-related factors and the prevalence of IA-related symptoms [ 8 , 9 , 10 ]. Furthermore, psychosocial problems seem to be related to subjective IAQ and IA-related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between building-related factors and perceived IAQ are well-documented (see e.g. Bakke et al, 2007;Simoni et al, 2016;Mečiarová et al, 2018). In workplaces, high work demands, poor work support and high stress are associated with decreased perceived IAQ (Brauer and Mikkelsen, 2010;Frontczak and Wargocki, 2011;Bluyssen et al, 2016).…”
Section: Background and Related Standardsmentioning
confidence: 99%